Effects of Individualized Psychological Support on Cognitive Function and Psychophysiological Stability Under Fatigue in Young Basketball Players - Zhou Ming-Yu; Olena Pavlyk; Iryna Masliak; Olga Riabchenko; Kateryna Hnatenko (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. To assess the effectiveness of an individualized psychological training programme as an intervention aimed at supporting recovery and maintaining cognitive performance and preventing psychophysiological exhaustion in basketball players aged 12–14 years during the annual macrocycle. Materials & Methods. The study involved 71 male basketball players aged 12–14 years at the basic training stage, who were divided into control (CG, n=35) and intervention (IG, n=36) groups. During the 52-week macrocycle (624 hours of total workload), a 52-hour (8.3% of the time) program of individualized psychological support was implemented in the IG, which included progressive muscle relaxation, diaphragmatic breathing, cognitive decompression and individual consultations. The CG followed the standard training programme without specialized psychological training. Assessment of verbal memory (Luria's "10-word" test), attention and mental stability (Schulte tables) was carried out under conditions of acute physical fatigue. Statistical analyses were performed using IBM SPSS Statistics version 26, using Student's t-test (p